2013
DOI: 10.1063/1.4821833
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of the ion beam production in a self magnetically insulated diode

Abstract: The paper presents the results of a study on shot to shot variation in energy density of an ion beam formed by a self-magnetically insulated diode with an explosive emission cathode. The experiments were carried out with the TEMP-4M accelerator operating in double-pulse mode: plasma formation occurs during the first pulse (negative polarity, 300-500 ns, 100-150 kV), and ion extraction and acceleration during the second pulse (positive polarity, 150 ns, 250-300 kV). Crucially, it was found that the standard dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The HPIB energy density instability was on average 24% at a diode system ser vice life of <10 pulses. Preliminary studies of the strip focusing diode with an EEC in the self magnetic insula tion mode showed that the SD of the beam energy den sity in a train of 50-100 pulses is at most 10-11% [6].…”
Section: Introductionmentioning
confidence: 99%
“…The HPIB energy density instability was on average 24% at a diode system ser vice life of <10 pulses. Preliminary studies of the strip focusing diode with an EEC in the self magnetic insula tion mode showed that the SD of the beam energy den sity in a train of 50-100 pulses is at most 10-11% [6].…”
Section: Introductionmentioning
confidence: 99%